Fundamentals of ophthalmic medical assisting - DuBois, Lindreth Grannis; American Academy of Ophthalmology (San Francisco : The Foundation of the American Academy of Ophthalmology, 1999)
Shows ophthalmic medical personnel how to perform a variety of basic tests so they can assume greater clinical responsibility
Author, Lindreth Grannis Dubois
Keywords: Eye Diseases -- diagnosis; Ophthalmic Assistants